Self-care activities among type 2 diabetes mellitus and glycaemic control in klinik pakar Perubatan, Hospital Universiti Sains Malaysia - Mamat, Rozila (Universiti Sains Malaysia, 2013)
The purpose of this cross-sectional study is to determine the self-care activities among type 2 diabetes mellitus and glycaemic control at Klinik Pakar Perubatan (KPP), Hospital USM. The health belief model was used as the theoretical framework of the study. 140 patients who were diagnosed with type 2 diabetes mellitus were allocated into this study. Before they enroll in this study, respondents were consented and being informed regarding the protocol of the study. A pilot study had been done among 30 respondents to check the reliability and validity of the study. Fasting blood sugar especially on HbAlc was also measured as the baseline’s data. Score of self-care activities was evaluated during the data analysis. The Spearman’s and Pearson correlation were used to test whether there was any significant association between score of self care activities practices and glycaemic control which involved the FBS and HbAlc. Before performing the analysis, data was tested in term of normality and fulfill several assumptions of correlation test. Then, the analysis shows that there was a significant association (p<0.05) with the negative correlation since r value were -0.468 for FBS and - 0.475 for HbAlc. The findings showed that majority of the respondents (61.4%) practice moderate self-care activities. Significant association was found between age, gender, educational and marital status to the self-care practices among type 2 diabetic patients. There is a need for health care professional to empower the knowledge and awareness of diabetic patients towards self-care activities. It is hope that this study will help to expand the knowledge and serve as a reference to help improve the management of diabetes in Malaysia as well as improve nursing service and related research.